Prolegomena zur Erforschung der Bedeutung der Eliteeinheiten im archaischen und klassischen Griechenland - Alonso, Víctor; Freitag, Klaus (Gerión. Revista de Historia Antigua, 2001)
Warfare in ancient Greece has been analysed in various different aspects, but no general treatment of elite corps in the citizen armies can be found in the modern research. This paper is a contribution to the study of theses selected troops in the archaic and classical periods. Sources and examples are discussed, and some possible future lines of research are proposed.